Legal Issues of Land Acquisition and Application of Risk Management in the Implementation of the Trans Sumatra Toll Road Project - Adi Faqdhi Akbar; Sadino Sadino; Aris Machmud (International Journal Labs, 2025)
The development of national strategic infrastructure demands legal certainty at every stage to support economic growth and equitable development. The Trans Sumatra Toll Road (JTTS) Project exemplifies this complexity, facing legal, social, and administrative challenges in land acquisition for the public interest. This study examines how the national legal framework for land acquisition is applied in the JTTS project and how law-based risk management supports its effectiveness in overcoming acquisition barriers. Using a juridical-normative approach focused on statutes, this research analyzes Law No. 2 of 2012 concerning Land Acquisition for Development for the Public Interest, Presidential Regulation No. 100 of 2014 jo. Presidential Regulation No. 42 of 2024 on Accelerating Toll Road Construction in Sumatra, and Supreme Court Regulation (PERMA) No. 3 of 2016 on Procedures for Objections to Land Acquisition Compensation, alongside case studies from the JTTS project. Findings reveal that although the legal framework provides a comprehensive basis, implementation faces regulatory disharmony, weak inter-agency coordination, and limited transparency in compensation. PERMA No. 3 of 2016 serves as a lex specialis, strengthening legal protection and certainty for affected communities. The study confirms that successful JTTS implementation depends on synergy between legal certainty and effective legal risk management. Reforming land law policy by harmonizing regulations, digitizing land data, and reinforcing the PERMA-based objection mechanism is a strategic step toward a fair and sustainable system for land acquisition.